Music-induced emotion effects on decision-making. (September 2019) - Palazzi, Ambra; Wagner Fritzen, Bruna; Gauer, Gustavo
This qualitative systematic review aimed to examine music-induced emotion effects on decision-making. Empirical articles published from 2006 to 2016 were searched for in PubMed and PsycInfo. Through the main search, 634 records were identified and 15 articles were included and analyzed according to the following categories: aims of the study, participants, study design, type of music, type of emotion, decision-making tasks, and study results. The included studies aimed to investigate the effects of music on prosociality and aggression, risk-taking, and other decision-making processes. All studies used experimental designs and most of them used pre-selected music and stimulation through music listening. Different decision-making tasks were used, such as a gambling task, helping behavior tasks, and even assessment of aggressive behavior through adding hot chili sauce to food. Results showed that music is a powerful and engaging stimulus that influences decision-making processes and risk-taking, promotes prosociality, and affects customers' behavioral choices. Different underlying processes in the interaction between music, mood, and decision-making are discussed. This review contributes to promoting research on the use of background music as an arousal and mood inducer in different contexts, as well as music-based interventions to foster prosociality and decrease aggressive behaviors.